A short-term longitudinal examination of the associations between self-control, delay of gratification and temporal considerations. (1st February 2017) - Watson, Samantha J.; Milfont, Taciano L.
Abstract: Greater ability to control ourselves, delay gratification and consider immediate and future consequences of our behaviors have been linked theoretically and empirically, yet evidence of their longitudinal relations is lacking. A sample of 345 undergraduate students completed a self-report survey twice within a five-month interval. Results from autoregressive cross-lagged analysis showed a bidirectional relation between self-control and delay of gratification, with self-control predicting change in delay of gratification and vice-versa, and these constructs differentially predicted change in temporal considerations. Self-control predicted change in consideration of immediate consequences, while delay of gratification predicted change in consideration of future consequences. These constructs are central to decision-making and successful human development, and the present study shows them to be temporally linked. Further longitudinal research is needed to examine the nature of their associations across long-term time frames. Highlights: Self-control, delay of gratification and temporal concern are empirically related. Their longitudinal relations were examined in a short-term panel data. Self-control and delay of gratification predict change in each other across time. Self-control predict change in consideration of immediate consequences. Delay of gratification predict change in consideration of future consequences.